The Influence of Free Cash Flow, Earning Per Share, and Debt to Equity Ratio on Stock Returns Moderated by Firm Size in IDX 30 Companies - Mahendra, Nanda; Jati, Dian Purnomo; Safitri, Julia (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study to analyze the effect of Free Cash Flow (FCF), Earning Per Share (EPS), and Debt to Equity Ratio (DER) on Stock Returns moderated by Firm Size in IDX 30 Companies. The purpose of this article is to prove the hypothesis of the influence between variables that will be used in further research..The results of this study indicate that  1) Earning  Per Share (EPS) has a positive effect on Stock Returns; 2) Free Cash Flow (FCF) has an effect on Stock Returns but in the opposite direction.; 3) Debt to Equity Ratio (DER) has no effect on Stock Returns; 4) Free Cash Flow (FCF) moderated by Firm Size has a positive effect on Stock Returns; 5) Earning Per Share (EPS) moderated by Firm Size has an effect on Stock Returns but in the opposite direction; 6) Debt to Equity Ratio (DER) moderated by Firm Size has a negative effect on Stock Returns.